Competition Juries as Intercultural Spaces - Carmela Cucuzzella (Footprint)
In this article, design competitions, as they are practiced in Canada, are understood as devices that allow the study of interdisciplinary and intercultural dimensions of architecture. From the construction of the brief to the selection of the winning project, competitions are exemplary platforms for communicating design values. For example, competitor project proposals, which comprise many qualities, including constructive, material, and even political, represent the priorities of each design team, in the form of a place. Jurors debate each of these qualities through their own expertise. In their search for excellence, the competition jury is then an exemplar contact zone. By examining the various documents produced in this process, we can uncover the value systems of the many stakeholders. Observations of jury deliberations and analyses of jury reports can help expose how the diversity of jurors influences the selection of the winning project. Furthermore, in a contemporary context where environmental design is at the forefront, this diversity is especially interesting to study. An environmental expert’s evaluation of quantitative eco-measurements is very different from an architect’s judgment of spatial qualities and experiences. The focus of this article is to understand how such a variety of jurors influences the competition outcome.